Long-life anti-wear grease and its use on automotive motor bearings

CN122686368APending Publication Date: 2026-09-04TONGYI PETROLEUM CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610725309.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-25
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

[0005]本发明旨在解决现有技术中润滑脂在汽车电机轴承高速、宽温及复杂工况下难以同时兼顾低磨损、长寿命与高低温性能平衡,且易发生基础油挥发、氧化稠化、微动磨损及疲劳剥落的问题

Benefits of technology

[0044]In this invention, the synergistic effect of composite calcium sulfonate thickener, high-alkalinity synthetic calcium sulfonate, and a specific ratio of ternary composite base oil enables the grease to maintain a stable colloidal structure over a wide temperature range. Regarding anti-wear properties, it integrates four anti-wear components to form a multi-layered, multi-mechanism composite lubricating film on the friction surface: modified nano-molybdenum disulfide, after double grafting, exhibits improved dispersibility and can form a strong chemical adsorption film; lanthanum-doped nano-cerium dioxide utilizes the oxygen vacancy regulation effect to enhance antioxidant and extreme pressure performance, while also acting as micro-ball bearings; a mixture of molybdenum dialkyldithiocarbamate, isobutylene sulfide, and tricresyl phosphate can sequentially form a physical adsorption film, a chemical reaction film, and a phosphate protective film; and the microcapsule component can release the lubricating medium as needed when the oil film ruptures. These four anti-wear mechanisms complement and synergize under different temperatures, loads, and lubrication conditions, resulting in a significant reduction in wear scar diameter and a significant extension of bearing life in the grease under high-speed, heavy-load conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122686368A_ABST
    Figure CN122686368A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lubricating grease, in particular to long-life anti-wear lubricating grease and application of the lubricating grease to automobile motor bearings. The lubricating grease is prepared from raw materials including a composite calcium sulfonate thickener 14-22%, high-alkaline-value synthetic calcium sulfonate 1.5-3.5%, surface-modified nano calcium carbonate 0.3-1.2%, a first anti-wear component 1.2-2.8%, a second anti-wear component 1.5-3.2%, a third anti-wear component 2-4%, a microcapsule component 1-2.5% and a balance of a composite base oil; the first anti-wear component includes modified nano molybdenum disulfide; the second anti-wear component includes lanthanum-doped nano cerium dioxide; the third anti-wear component includes a mixture of molybdenum dialkyldithiocarbamate, sulfided isobutylene and phosphoric acid trimethylphenyl ester; and the composite base oil is a ternary mixture of poly-alpha-olefin, alkylated naphthalene and partial benzene triacid ester. The lubricating grease has long life and anti-wear performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lubricating grease technology, specifically to a long-life anti-wear grease and its application in automotive motor bearings. Background Technology

[0002] As the core lubricating medium for automotive motor bearings, grease's performance directly affects the motor's operating efficiency, service life, and reliability. With the rapid development of new energy vehicles and intelligent driving technologies, automotive motors are evolving towards higher power density, higher speeds, miniaturization, and longer maintenance cycles. This places higher demands on the wear resistance, high-temperature stability, and durability of greases. Especially in drive motor bearings, greases must simultaneously withstand high-speed shearing, fretting wear, high-temperature oxidation, and boundary lubrication conditions caused by frequent start-stop cycles. Therefore, developing a grease that balances excellent anti-wear performance with long service life has become a pressing technical problem in this field.

[0003] Currently, existing greases used in automotive motor bearings primarily employ lithium-based or lithium-complex thickeners, combined with mineral oil or partially synthetic oils as the base oil, and add molybdenum disulfide, graphite, or zinc-based anti-wear agents to enhance extreme pressure anti-wear performance. However, under long-term high-speed operation, these greases are susceptible to base oil evaporation loss, oxidative thickening, and shear softening, which may lead to lubricating film rupture and affect bearing service life. Furthermore, some conventional anti-wear additives may produce corrosive byproducts at high temperatures, potentially exacerbating bearing surface fatigue spalling. To extend grease life, some solutions attempt to increase base oil viscosity or antioxidant dosage; however, this often comes at the cost of sacrificing low-temperature starting performance. Other solutions introduce nano-solid additives, but nanoparticles are prone to agglomeration and have poor dispersion stability, resulting in unsatisfactory long-term effects. In practical applications, a further balance needs to be struck between starting torque and low-temperature starting performance. On the other hand, while some literature reports solutions using polyurea thickeners or complex calcium sulfonate systems to improve high-temperature resistance, existing technologies still have room for improvement in simultaneously enhancing resistance to fretting wear and fatigue spalling.

[0004] Therefore, there is an urgent need to develop a grease that can simultaneously meet the requirements of high wear resistance, long service life, and wide temperature range adaptability, so as to meet the long-term reliable operation requirements of automotive motor bearings under high speed, wide temperature and complex working conditions. Summary of the Invention

[0005] This invention aims to solve the problems of existing lubricating greases in automotive motor bearings, which struggle to simultaneously achieve a balance between low wear, long lifespan, and high and low temperature performance under high-speed, wide-temperature, and complex operating conditions, and are prone to base oil evaporation, oxidative thickening, fretting wear, and fatigue spalling. To achieve this objective, this invention provides a long-life anti-wear lubricating grease and its applications.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] A long-life anti-wear grease is prepared by the following steps:

[0008] Step 1: Weigh the following raw material components by mass percentage:

[0009] The composition consists of: 14%-22% compound calcium sulfonate thickener, 1.5%-3.5% high-alkalinity synthetic calcium sulfonate, 0.3%-1.2% surface-modified nano-calcium carbonate, 1.2%-2.8% first anti-wear component, 1.5%-3.2% second anti-wear component, 2%-4% third anti-wear component, 1%-2.5% microencapsulation component, and the balance being compound base oil.

[0010] The first anti-wear component comprises modified nano-molybdenum disulfide; the second anti-wear component comprises lanthanum-doped nano-cerium dioxide; the third anti-wear component comprises a mixture of molybdenum dialkyldithiocarbamate, isobutylene sulfide, and tricresyl phosphate; the composite base oil comprises a ternary mixture of polyalphaolefin, alkyl naphthalene, and trimellitic acid ester, wherein the mass ratio of polyalphaolefin, alkyl naphthalene, and trimellitic acid ester is 1:(0.4-0.6):(0.2-0.4); and the microcapsule component comprises resin-coated vegetable oil microcapsules.

[0011] Step 2: Mix the complex calcium sulfonate thickener with the complex base oil, stir, add high-alkalinity synthetic calcium sulfonate, surface-modified nano calcium carbonate, first anti-wear component, second anti-wear component, third anti-wear component, and microcapsule component, continue stirring and grinding to obtain a long-life anti-wear grease.

[0012] Preferably, the high-alkalinity synthetic calcium sulfonate is a long-chain linear alkylbenzene high-alkalinity synthetic calcium sulfonate with a total alkalinity of 380-450 mg KOH / g.

[0013] Preferably, the composite calcium sulfonate thickener in step one is generated by converting high-alkalinity synthetic calcium sulfonate, and the conversion process includes:

[0014] (1) Weigh out high-alkalinity synthetic calcium sulfonate, composite base oil, 12-hydroxystearic acid, calcium hydroxide emulsion, acetic acid, boric acid solution, and water. The mass ratio of high-alkalinity synthetic calcium sulfonate, composite base oil, 12-hydroxystearic acid, calcium hydroxide emulsion, acetic acid, boric acid solution, and water is (20-30):(15-25):(2-5):(100-250):(2-5):(60-120):(10-20).

[0015] (2) Mix high-alkalinity synthetic calcium sulfonate, composite base oil and acetic acid, and react at 90-100℃ until no bubbles are generated, then maintain the temperature at 90-100℃ and continue the reaction for 20-40 minutes.

[0016] (3) Add calcium hydroxide emulsion and stir;

[0017] (4) Add boric acid solution and stir;

[0018] (5) Add 12-hydroxystearic acid and carry out saponification reaction at 110-120℃ for 40-60 min.

[0019] (6) Heat to 180℃ and carry out the puffing reaction for 40-50 minutes;

[0020] (7) Heat to 225-235℃ and carry out high-temperature refining for 20-30 minutes;

[0021] (8) Cool down to below 150℃ and grind and homogenize to obtain a composite calcium sulfonate thickener.

[0022] Preferably, the high-alkalinity synthetic calcium sulfonate and the composite base oil are the same as the high-alkalinity synthetic calcium sulfonate and composite base oil in the raw material components for preparing long-life anti-wear grease.

[0023] Preferably, the calcium hydroxide emulsion is prepared by mixing calcium hydroxide and water at a weight ratio of 1:49, and the boric acid solution is prepared by mixing boric acid and water at a weight ratio of 1:19.

[0024] Preferably, the surface-modified nano-calcium carbonate includes KH560 in-situ modified nano-calcium carbonate, which is prepared by the following steps:

[0025] (1) Mix silane coupling agent KH560 (3-glycidyl ether oxypropyl trimethoxysilane) with an aqueous ethanol solution, adjust the pH value to 4-5, and hydrolyze at 50-60℃ for 30-60 min to obtain silane hydrolysate;

[0026] Nano-calcium carbonate was mixed with ethanol and ultrasonically dispersed to obtain a nano-calcium carbonate suspension.

[0027] (2) Add the silane hydrolysate dropwise to the nano calcium carbonate suspension under stirring, and react at 50-70℃ for 4-6h. After the reaction is completed, centrifuge, wash and dry to obtain 3-glycidyl etheroxypropyl)trimethoxysilane in-situ modified nano calcium carbonate.

[0028] Preferably, the amount of silane coupling agent KH560 added is 3%-8% of the mass of nano-calcium carbonate.

[0029] Preferably, the modified nano-molybdenum disulfide comprises aminosilane-dithiocarbamate double-grafted modified nano-molybdenum disulfide, which is prepared by the following steps:

[0030] (1) Mix nano-molybdenum disulfide with an ethanol aqueous solution, disperse by ultrasonication, add silane coupling agent KH550, adjust the pH value to 4-5, react at 60-80℃ for 4-6h, after the reaction is completed, centrifuge and wash to obtain aminosilane grafted modified nano-molybdenum disulfide intermediate.

[0031] (2) The aminosilane-grafted modified molybdenum disulfide intermediate was dispersed in ethanol, the pH value was adjusted to 9-10 with sodium hydroxide, carbon disulfide was added, and the reaction was stirred at 25-40℃ for 2-4 hours. After the reaction was completed, the intermediate was centrifuged, washed, and dried to obtain aminosilane-dithiocarbamate double-grafted modified molybdenum disulfide nanoparticles.

[0032] The amount of silane coupling agent KH550 added is 2%-4% of the mass of nano molybdenum disulfide, and the amount of carbon disulfide added is 1.5%-3% of the mass of nano molybdenum disulfide;

[0033] Preferably, in the lanthanum-doped nano-cerium dioxide, the molar ratio of lanthanum to cerium is (0.05-0.15):1, and it is prepared by the following steps:

[0034] Weigh out cerium nitrate hexahydrate and lanthanum nitrate hexahydrate in a molar ratio of lanthanum to cerium of (0.05-0.15):1, dissolve them in deionized water, and add ammonium bicarbonate aqueous solution dropwise under stirring to carry out a precipitation reaction. At the same time, adjust the pH of the reaction system to 8-9 with ammonia. After the reaction is completed, centrifuge, wash, dry, and calcine at 500℃ for 3 hours to obtain lanthanum-doped nano-cerium dioxide.

[0035] In this process, ammonium bicarbonate aqueous solution acts as a precipitant, converting cerium ions and lanthanum ions into carbonate precipitates. Adjusting the pH of the reaction system to 8-9 can ensure the precipitation efficiency of ammonium bicarbonate, prevent the formation of hydroxides, and achieve uniform doping of lanthanum in the cerium dioxide lattice.

[0036] Preferably, in the mixture of molybdenum dialkyldithiocarbamate, isobutylene sulfide, and tricresyl phosphate, the mass ratio of molybdenum dialkyldithiocarbamate, isobutylene sulfide, and tricresyl phosphate is 1:(0.5-1):(0.3-0.7), wherein the molybdenum content in molybdenum dialkyldithiocarbamate is 8%-12% by mass, and the sulfur content in isobutylene sulfide is 40%-48% by mass.

[0037] Preferably, the resin-coated vegetable oil microcapsules include castor oil microcapsules coated with phenolic resin;

[0038] The phenolic resin-coated castor oil microcapsules are prepared by the following steps:

[0039] (1) Take phenol and formaldehyde aqueous solution (37%-40%) in a molar ratio of 1:(1.2-1.8), mix them, add 5%-15% ammonia water of phenol mass, stir and react at 60-70℃ for 30-60 min to obtain water-soluble phenolic resin prepolymer;

[0040] Take castor oil and emulsifier at a mass ratio of 100:(2-5), add 2-4 times the mass of castor oil to water, and emulsify at a high speed of 8000-10000 r / min for 20-40 min at a temperature of 40-60℃ to obtain an oil-in-water emulsion.

[0041] (2) Add water-soluble phenolic resin prepolymer to the oil-in-water emulsion. The amount of water-soluble phenolic resin prepolymer added is 25%-50% of the mass of castor oil. The addition time is 10-20 min. Stir evenly and adjust the pH value to 4-6 so that the prepolymer undergoes a polycondensation reaction on the surface of the oil droplets. Gradually increase the temperature to 90℃ at a heating rate of 2-5℃ / min. After reaching 90℃, continue to keep the temperature for 2-4 h. After the reaction is completed, cool naturally to room temperature, separate, wash, and dry to obtain phenolic resin-coated castor oil microcapsules.

[0042] The application of a long-life anti-wear grease, as described above, in automotive motor bearings.

[0043] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0044] In this invention, the synergistic effect of composite calcium sulfonate thickener, high-alkalinity synthetic calcium sulfonate, and a specific ratio of ternary composite base oil enables the grease to maintain a stable colloidal structure over a wide temperature range. Regarding anti-wear properties, it integrates four anti-wear components to form a multi-layered, multi-mechanism composite lubricating film on the friction surface: modified nano-molybdenum disulfide, after double grafting, exhibits improved dispersibility and can form a strong chemical adsorption film; lanthanum-doped nano-cerium dioxide utilizes the oxygen vacancy regulation effect to enhance antioxidant and extreme pressure performance, while also acting as micro-ball bearings; a mixture of molybdenum dialkyldithiocarbamate, isobutylene sulfide, and tricresyl phosphate can sequentially form a physical adsorption film, a chemical reaction film, and a phosphate protective film; and the microcapsule component can release the lubricating medium as needed when the oil film ruptures. These four anti-wear mechanisms complement and synergize under different temperatures, loads, and lubrication conditions, resulting in a significant reduction in wear scar diameter and a significant extension of bearing life in the grease under high-speed, heavy-load conditions.

[0045] Based on the above-mentioned synergistic mechanism, by optimizing the mass percentage of each component, this invention ensures the effective concentration of additives while avoiding abnormal consistency or component antagonism caused by excessive addition, thus achieving a balance between long service life and anti-wear performance in the grease as a whole. Attached Figure Description

[0046] Figure 1 This is a scanning electron microscope image of the phenolic resin-coated castor oil microcapsules prepared in Example 7;

[0047] Figure 2 The graph shows the results of the cone penetration and anti-wear properties of the grease samples prepared in Examples 8-10 and Comparative Examples 1-10.

[0048] Figure 3 The graph shows the results of the extreme pressure performance determination of the grease samples prepared in Examples 8-10 and Comparative Examples 1-10;

[0049] Figure 4 The graph shows the results of the low-temperature torque measurement of the grease samples prepared in Examples 8-10 and Comparative Examples 1-10. Detailed Implementation

[0050] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0051] Example 1

[0052] This embodiment discloses a composite calcium sulfonate thickener, which is generated by converting high-alkalinity synthetic calcium sulfonate. The conversion process includes:

[0053] (1) Weigh out the following: high-alkalinity synthetic calcium sulfonate (T106D, using long-chain (C20-24) linear alkylbenzene sulfonic acid as raw material, total alkalinity ≥395mgKOH / g, calcium content ≥14%), composite base oil, 12-hydroxystearic acid (CAS No.: 106-14-9), calcium hydroxide emulsion (calcium hydroxide and water are mixed at a weight ratio of 1:49), acetic acid, boric acid solution (boric acid and water are mixed at a weight ratio of 1:19, heated to 80℃ and stirred until completely dissolved, cooled to 50℃ for later use), water, and the mass ratio of high-alkalinity synthetic calcium sulfonate, composite base oil, 12-hydroxystearic acid, calcium hydroxide emulsion, acetic acid, boric acid solution and water is 25:20:3.5:180:4:90:15;

[0054] The composite base oil is a ternary mixture formed by mixing polyalphaolefin (polyalphaolefin PAO-6, with a kinematic viscosity of 5.9 cSt at 100℃), 1-dodecylnaphthalene, and tris(2-ethylhexyl) 1,2,4-benzenetricarboxylate (CAS No.: 3319-31-1) in a mass ratio of 1:0.4:0.2.

[0055] (2) Mix high-alkalinity synthetic calcium sulfonate, composite base oil and acetic acid, and react at 95°C until no bubbles are generated, then maintain the temperature at 95°C and continue the reaction for 30 minutes.

[0056] (3) Add calcium hydroxide emulsion and stir at a stirring speed of 300 r / min for 30 min;

[0057] (4) Add boric acid solution and stir at a stirring speed of 300 r / min for 30 min;

[0058] (5) Add 12-hydroxystearic acid and carry out saponification reaction at 115℃ for 50 min;

[0059] (6) Heat to 180℃ for puffing reaction, and the reaction time is 45 min;

[0060] (7) Heat to 230℃ for high-temperature refining for 25 minutes;

[0061] (8) Stir and cool down to below 150°C, then grind and homogenize three times with a three-roll mill (grinding gaps of 50μm, 20μm and 10μm respectively) to obtain a composite calcium sulfonate thickener.

[0062] Example 2

[0063] This embodiment discloses a composite calcium sulfonate thickener, which differs from Example 1 only in that the composite base oil is a ternary mixture formed by mixing poly-α-olefin, 1-dodecylnaphthalene and tris(2-ethylhexyl) 1,2,4-benzenetricarboxylate in a mass ratio of 1:0.6:0.4, while other conditions remain unchanged.

[0064] Example 3

[0065] This embodiment discloses a composite calcium sulfonate thickener, which differs from Example 1 only in that the composite base oil is a ternary mixture formed by mixing poly-α-olefin, 1-dodecylnaphthalene and tris(2-ethylhexyl) 1,2,4-benzenetricarboxylate in a mass ratio of 1:0.5:0.3, while other conditions remain unchanged.

[0066] Example 4

[0067] This embodiment discloses a surface-modified nano-calcium carbonate, wherein the surface-modified nano-calcium carbonate is KH560 in-situ modified nano-calcium carbonate, and the KH560 in-situ modified nano-calcium carbonate is prepared by the following steps:

[0068] (1) Mix silane coupling agent KH560 with 90wt% ethanol aqueous solution at a mass ratio of 1:10, adjust the pH value to 4.5 with acetic acid, and hydrolyze at 55℃ for 45min to obtain silane hydrolysate;

[0069] Nano-calcium carbonate (average particle size 95±5nm) was mixed with ethanol at a mass ratio of 1:10 and ultrasonically dispersed at a frequency of 50kHz for 30min to obtain a nano-calcium carbonate suspension.

[0070] The amount of silane coupling agent KH560 used is 6% of the mass of nano-calcium carbonate;

[0071] (2) Add the silane hydrolysate dropwise to the nano calcium carbonate suspension under stirring at 300 r / min, react at 60 ℃ for 5 h, centrifuge after the reaction, wash the centrifuged precipitate with ethanol 3 times, and dry it in a vacuum drying oven at 60 ℃ to constant weight to obtain KH560 in-situ modified nano calcium carbonate.

[0072] Example 5

[0073] This embodiment discloses a modified nano-molybdenum disulfide, wherein the modified nano-molybdenum disulfide is an aminosilane-dithiocarbamate double-grafted modified nano-molybdenum disulfide, which is prepared by the following steps:

[0074] Nano-sized molybdenum disulfide (average particle size of 200 nm) was mixed with 90 wt% ethanol aqueous solution at a mass ratio of 1:10. After ultrasonic dispersion at 50 kHz for 30 min, silane coupling agent KH550 (γ-aminopropyltriethoxysilane) was added. The pH value was adjusted to 4.5 with acetic acid and reacted at 70 ℃ for 5 h. After the reaction was completed, the mixture was centrifuged and the precipitate was washed three times with ethanol to obtain aminosilane grafted modified nano-molybdenum disulfide intermediate.

[0075] Aminosilane-grafted modified molybdenum disulfide nano intermediates were dispersed in ethanol at a mass ratio of 1:10. The pH was adjusted to 9.5 with sodium hydroxide, and carbon disulfide was added. The mixture was stirred at 35°C for 3 hours. After the reaction was completed, the mixture was centrifuged, and the precipitate was washed three times with ethanol and dried in a vacuum drying oven at 60°C until constant weight was obtained to yield aminosilane-dithiocarbamate double-grafted modified molybdenum disulfide nano.

[0076] The amount of silane coupling agent KH550 added is 3% of the mass of nano molybdenum disulfide, and the amount of carbon disulfide added is 2.5% of the mass of nano molybdenum disulfide.

[0077] Example 6

[0078] This embodiment discloses a lanthanum-doped cerium dioxide nanoparticle, which is prepared by the following steps:

[0079] Weigh out cerium nitrate hexahydrate and lanthanum nitrate hexahydrate in a molar ratio of lanthanum to cerium of 0.1:1, dissolve them in deionized water to obtain a mixed salt solution. The amount of deionized water used is such that the total concentration of metal ions in the mixed salt solution is 0.5 mol / L. Under stirring, add ammonium bicarbonate aqueous solution (1.5 mol / L) dropwise to carry out the precipitation reaction. The amount of ammonium bicarbonate aqueous solution added is such that the molar ratio of ammonium bicarbonate to the total metal ions in the mixed salt solution is 3:1. At the same time, adjust the pH of the reaction system to 9 with ammonia water (specification: 25 wt%). After the reaction is completed, centrifuge, centrifuge the precipitate, wash it three times with deionized water and anhydrous ethanol, dry it in a vacuum drying oven at 60℃ to constant weight, and then calcine it at 500℃ for 3 hours to obtain lanthanum-doped nano-cerium dioxide.

[0080] Example 7

[0081] This embodiment discloses a resin-coated vegetable oil microcapsule, which is prepared by the following steps:

[0082] (1) Take phenol and formaldehyde aqueous solution (specification: 37wt%) in a molar ratio of 1:1.5, mix them, add 10% ammonia water (specification: 25wt%) of the mass of phenol, stir and react at 65℃ for 45min to obtain water-soluble phenolic resin prepolymer;

[0083] Take castor oil and emulsifier (OP-10) at a mass ratio of 100:3.5, add water with a mass of 3 times that of castor oil, and emulsify at 50°C and a high speed of 9000 r / min for 30 min to obtain an oil-in-water emulsion.

[0084] (2) The water-soluble phenolic resin prepolymer was added dropwise to the oil-in-water emulsion. The amount of water-soluble phenolic resin prepolymer added was 40% of the mass of castor oil. The addition time was 15 min. After stirring evenly, the pH value was adjusted to 5 with 5 wt% dilute hydrochloric acid to allow the prepolymer to undergo a polycondensation reaction on the surface of the oil droplets. The temperature was gradually increased to 90℃ at a heating rate of 3℃ / min. After reaching 90℃, the temperature was maintained for 3 h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged. The centrifuged precipitate was washed three times with deionized water and ethanol, and then dried in a vacuum drying oven at 60℃ until constant weight was obtained to obtain resin-coated vegetable oil microcapsules.

[0085] Example 8

[0086] This embodiment discloses a long-life anti-wear grease, which is prepared by the following steps:

[0087] Step 1: Weigh the following raw material components by mass percentage:

[0088] The composition consists of 14% complex calcium sulfonate thickener, 1.5% high-alkalinity synthetic calcium sulfonate, 0.3% surface-modified nano calcium carbonate, 1.2% first anti-wear component, 1.5% second anti-wear component, 2% third anti-wear component, 1% microencapsulation component, and the balance being complex base oil (78.5%).

[0089] Among them, the composite calcium sulfonate thickener is the composite calcium sulfonate thickener prepared in Example 1, the high-alkalinity synthetic calcium sulfonate is the same as the high-alkalinity synthetic calcium sulfonate used in Example 1, the surface-modified nano calcium carbonate is the KH560 in-situ modified nano calcium carbonate prepared in Example 4, the first anti-wear component is the modified nano molybdenum disulfide prepared in Example 5, the second anti-wear component is the lanthanum-doped nano cerium dioxide prepared in Example 6, the third anti-wear component is a mixture formed by mixing molybdenum dialkyl dithiocarbamate (molybdenum mass content is 10%), isobutylene sulfide (sulfur mass content is 44%) and tricresyl phosphate (CAS No.: 1330-78-5) in a mass ratio of 1:0.5:0.3, and the microcapsule component is the resin-coated vegetable oil microcapsule prepared in Example 7;

[0090] Step 2: Mix the complex calcium sulfonate thickener with the complex base oil and stir at 200 r / min for 30 min at 60℃. Add high-alkalinity synthetic calcium sulfonate, surface-modified nano calcium carbonate, first anti-wear component, second anti-wear component, third anti-wear component, and microcapsule component. Continue stirring at 200 r / min for 30 min at 60℃. After stirring, use a colloid mill with a gap of 0.15 mm and a speed of 10000 r / min to ensure that the material completely passes through the mill head as one cycle. Repeat this process three times to obtain a long-life anti-wear grease.

[0091] Example 9

[0092] This embodiment discloses a long-life anti-wear grease, which is prepared by the following steps:

[0093] Step 1: Weigh the following raw material components by mass percentage:

[0094] The composition consists of 22% compound calcium sulfonate thickener, 3.5% high-alkalinity synthetic calcium sulfonate, 1.2% surface-modified nano calcium carbonate, 2.8% first anti-wear component, 3.2% second anti-wear component, 4% third anti-wear component, 2.5% microencapsulated component, and the balance being compound base oil (60.8%).

[0095] Among them, the composite calcium sulfonate thickener is the composite calcium sulfonate thickener prepared in Example 2, the high-alkalinity synthetic calcium sulfonate is the same as the high-alkalinity synthetic calcium sulfonate used in Example 1, the surface-modified nano calcium carbonate is the KH560 in-situ modified nano calcium carbonate prepared in Example 4, the first anti-wear component is the modified nano molybdenum disulfide prepared in Example 5, the second anti-wear component is the lanthanum-doped nano cerium dioxide prepared in Example 6, the third anti-wear component is a mixture formed by mixing molybdenum dialkyl dithiocarbamate (molybdenum mass content is 10%), isobutylene sulfide (sulfur mass content is 44%) and tricresyl phosphate (CAS No.: 1330-78-5) in a mass ratio of 1:1:0.7, and the microcapsule component is the resin-coated vegetable oil microcapsule prepared in Example 7;

[0096] Step 2: Mix the composite calcium sulfonate thickener with the composite base oil and stir at 300 r / min for 20 min at 80℃. Add high-alkalinity synthetic calcium sulfonate, surface-modified nano calcium carbonate, first anti-wear component, second anti-wear component, third anti-wear component, and microcapsule component. Continue stirring at 300 r / min for 20 min at 80℃. After stirring, use a colloid mill with a gap of 0.15 mm and a speed of 10000 r / min to ensure that the material completely passes through the mill head once. Repeat this process three times to obtain a long-life anti-wear grease.

[0097] Example 10

[0098] This embodiment discloses a long-life anti-wear grease, which is prepared by the following steps:

[0099] Step 1: Weigh the following raw material components by mass percentage:

[0100] The composition consists of 18% complex calcium sulfonate thickener, 2.5% high-alkalinity synthetic calcium sulfonate, 0.8% surface-modified nano calcium carbonate, 2% first anti-wear component, 2.4% second anti-wear component, 3% third anti-wear component, 1.8% microencapsulated component, and the balance being complex base oil (69.5%).

[0101] Among them, the composite calcium sulfonate thickener is the composite calcium sulfonate thickener prepared in Example 3, the high-alkalinity synthetic calcium sulfonate is the same as the high-alkalinity synthetic calcium sulfonate used in Example 1, the surface-modified nano calcium carbonate is the KH560 in-situ modified nano calcium carbonate prepared in Example 4, the first anti-wear component is the modified nano molybdenum disulfide prepared in Example 5, the second anti-wear component is the lanthanum-doped nano cerium dioxide prepared in Example 6, the third anti-wear component is a mixture formed by mixing molybdenum dialkyl dithiocarbamate (molybdenum mass content is 10%), isobutylene sulfide (sulfur mass content is 44%) and tricresyl phosphate (CAS No.: 1330-78-5) in a mass ratio of 1:1:0.7, and the microcapsule component is the resin-coated vegetable oil microcapsule prepared in Example 7;

[0102] Step 2: Mix the composite calcium sulfonate thickener with the composite base oil and stir at 250 r / min for 25 min at 70℃. Add high-alkalinity synthetic calcium sulfonate, surface-modified nano calcium carbonate, first anti-wear component, second anti-wear component, third anti-wear component, and microcapsule component. Continue stirring at 250 r / min for 25 min at 70℃. After stirring, use a colloid mill with a gap of 0.15 mm and a speed of 10000 r / min to ensure that the material completely passes through the mill head once. Repeat this process three times to obtain a long-life anti-wear grease.

[0103] Comparative Example 1

[0104] This comparative example discloses a long-life anti-wear grease, which differs from Example 8 only in that the surface-modified nano-calcium carbonate is replaced with unmodified nano-calcium carbonate (the same as the nano-calcium carbonate in Example 4), while other conditions remain unchanged.

[0105] Comparative Example 2

[0106] This comparative example discloses a long-life anti-wear grease, which differs from Example 8 only in that the first anti-wear component is replaced by unmodified nano-molybdenum disulfide (the same as the nano-molybdenum disulfide in Example 5) instead of aminosilane-dithiocarbamate double-grafted modified nano-molybdenum disulfide, while other conditions remain unchanged.

[0107] Comparative Example 3

[0108] This comparative example discloses a long-life anti-wear grease, which differs from Example 8 only in that the second anti-wear component is replaced by undoped lanthanum nano-cerium dioxide (preparation method is the same as in Example 6, but without the addition of lanthanum hexahydrate nitrate), while other conditions remain unchanged.

[0109] Comparative Example 4

[0110] This comparative example discloses a long-life anti-wear grease, which differs from Example 8 only in that: no microcapsule components are added, and the missing mass is made up by a composite base oil, that is, the mass percentage of the composite base oil is 79.5%, and other conditions remain unchanged.

[0111] Comparative Example 5

[0112] This comparative example discloses a long-life anti-wear grease, which differs from Example 8 only in that the mass ratio of molybdenum dialkyl dithiocarbamate, isobutylene sulfide, and tricresyl phosphate in the third anti-wear component is changed from 1:0.5:0.3 in Example 8 to 1:0.2:0.1, while other conditions remain unchanged.

[0113] Comparative Example 6

[0114] This comparative example discloses a long-life anti-wear grease, which differs from Example 8 only in that: no third anti-wear component (molybdenum dialkyl dithiocarbamate, isobutylene sulfide, and tricresyl phosphate are added), and the missing mass is made up by the composite base oil, while other conditions remain unchanged.

[0115] Comparative Example 7

[0116] This comparative example discloses a long-life anti-wear grease, which differs from Example 8 only in that the third anti-wear component is only molybdenum dialkyl dithiocarbamate (the amount added is still 2%), without sulfurized isobutylene and tricresol phosphate, and other conditions remain unchanged.

[0117] Comparative Example 8

[0118] This comparative example discloses a long-life anti-wear grease, which differs from Example 8 only in that the ternary mixture formed by mixing polyalphaolefin, 1-dodecylnaphthalene and tris(2-ethylhexyl) 1,2,4-benzenetricarboxylate in a mass ratio of 1:0.4:0.2 is replaced with a single polyalphaolefin PAO-6, while other conditions remain unchanged.

[0119] Comparative Example 9

[0120] This comparative example discloses a long-life anti-wear grease, which differs from Example 8 only in that the raw material composition is adjusted to 10% of complex calcium sulfonate thickener, 0.8% of high-alkalinity synthetic calcium sulfonate, 0.1% of surface-modified nano calcium carbonate, 0.5% of the first anti-wear component, 0.6% of the second anti-wear component, 0.8% of the third anti-wear component, 0.3% of the microcapsule component, and the balance being a complex base oil (86.9%), while other conditions remain unchanged.

[0121] Comparative Example 10

[0122] This comparative example discloses a long-life anti-wear grease, which differs from Example 8 only in that the raw material composition is adjusted to 30% of complex calcium sulfonate thickener, 5% of high-alkalinity synthetic calcium sulfonate, 2% of surface-modified nano calcium carbonate, 5% of the first anti-wear component, 5% of the second anti-wear component, 6% of the third anti-wear component, 4% of the microcapsule component, and the balance is complex base oil (43%), while other conditions remain unchanged.

[0123] Test case

[0124] The performance of the grease samples prepared in Examples 8-10 and Comparative Examples 1-10 was determined:

[0125] (1) Determine the cone penetration: Refer to standard GB / T269-2023. Under constant temperature of 25℃, fill the working cup with the grease sample and perform 60 full-stroke reciprocating shearings within 60s to determine the cone penetration (0.1mm).

[0126] (2) Determine the dropping point: Refer to standard GB / T3498-2008, put the grease sample into the grease cup, heat it at a constant rate, and record the temperature (°C) when the first drop of oil drips from the grease cup hole.

[0127] (3) Determination of anti-wear performance: The anti-wear performance of the grease sample was determined according to the standard SH / T0204-1992: the speed of the four-ball machine was 1200 r / min, the room temperature was 392 N, the test time was 60 min, and the diameter of the steel ball wear scar (mm) was determined.

[0128] (4) Determination of extreme pressure performance: Determination of extreme pressure performance of grease samples in accordance with standard GB / T3142-2019: The load was gradually increased on a four-ball machine to determine the maximum non-seize load (PB value, N) and sintering load (PD value, N).

[0129] (5) Determination of evaporation loss: Refer to standard GB / T7325-1987 to determine the evaporation loss of grease samples: Place the grease sample in an evaporating dish, keep it at 150℃ for 22h, and determine the percentage of mass loss (%).

[0130] (6) Determination of oxidation stability: Refer to standard SH / T0325-1992 to determine the oxidation stability of the grease sample: Place the grease sample in an oxygen bomb, keep it at 99℃, fill it with oxygen to 0.76MPa, and measure the pressure drop (kPa) within 100h.

[0131] (7) Determine the low temperature torque: Refer to standard SH / T0338-1992 to determine the low temperature torque of the grease sample: Put the grease sample into the 6204 ball bearing, and measure the starting torque (N·m) and running torque (N·m) after keeping it at -40℃ for 4 hours.

[0132] (8) Determine bearing life: Refer to the standard ASTM D3336 to determine the service life of grease samples in automotive motor bearings: Put grease samples into 6204 bearings, run them at 120℃ and 10000r / min, and record the time (h) when the bearings experience temperature rise or abnormal torque. This is the bearing life.

[0133] The performance test results are shown in Table 1:

[0134] Table 1

[0135] Cone penetration (0.1mm) 285 272 278 288 286 284 283 286 282 284 278 312 245 Dropping point (°C) >320 >320 >320 >320 >320 >320 >320 >320 312 315 >320 298 >320 Wear scar diameter (mm) 0.42 0.38 0.4 0.51 0.55 0.49 0.52 0.48 0.61 0.58 0.56 0.62 0.41 PB value (N) 882 980 921 784 745 823 833 843 686 706 735 588 882 PD value (N) 3087 3087 3087 2450 2450 3087 3087 2450 1960 1960 2450 1960 3087 Percentage of quality loss (%) 1.65 1.52 1.58 1.72 1.7 1.68 1.75 1.67 1.69 1.68 2.54 2.18 1.48 Pressure drop (kPa) 28 24 26 32 30 29 33 29 31 30 31 35 25 Starting torque (N·m) 0.52 0.58 0.55 0.54 0.53 0.53 0.55 0.53 0.54 0.53 0.89 0.48 0.78 Operating torque (N·m) 0.21 0.23 0.22 0.22 0.22 0.21 0.23 0.21 0.22 0.21 0.38 0.18 0.32 Bearing life (h) 1850 2100 1980 1320 1180 1520 1350 1420 890 950 960 720 1560

[0136] As shown in Table 1, the grease prepared by this invention exhibits excellent high and low temperature performance, anti-wear properties, extreme pressure performance, and long service life. The dropping points of Examples 8-10 are all greater than 320℃, indicating that the complex calcium sulfonate thickener imparts excellent high-temperature stability to the grease; the wear scar diameter is between 0.38-0.42 mm, the PB value is between 882-980 N, and the PD value reaches 3087 N, indicating a significant synergistic effect of the four anti-wear components; the evaporation loss at 150℃ is only 1.52%-1.65%, indicating that the ternary composite base oil has excellent low volatility; the starting torque at -40℃ is 0.52-0.58 N·m, and the running torque is 0.21-0.23 N·m, indicating good low-temperature starting performance; the bearing life reaches 1850-2100 hours. Compared to Example 8, in Comparative Example 1, after replacing the surface-modified nano-calcium carbonate with unmodified nano-calcium carbonate, the wear scar diameter increased from 0.42 mm to 0.51 mm, the PB value decreased from 882 N to 784 N, the PD value decreased from 3087 N to 2450 N, the oxidation stability deteriorated (pressure drop increased from 28 kPa to 32 kPa), and the bearing life decreased from 1850 h to 1320 h. This indicates that the in-situ modification with KH560 significantly improved the dispersibility of nano-calcium carbonate in the base oil, while the unmodified nano-calcium carbonate was prone to agglomeration and could not effectively exert its properties. It has auxiliary thickening and anti-wear effects. In Comparative Example 2, after replacing the aminosilane-dithiocarbamate double-grafted modified nano-molybdenum disulfide with unmodified nano-molybdenum disulfide, the wear scar diameter increased from 0.42 mm to 0.55 mm, the PB value decreased from 882 N to 745 N, the PD value decreased from 3087 N to 2450 N, and the bearing life decreased from 1850 h to 1180 h. This indicates that the double-grafting modification significantly improved the dispersibility and surface reactivity of nano-molybdenum disulfide in the base oil, while unmodified nano-molybdenum disulfide was difficult to form a stable chemisorption film. The anti-wear effect was significantly reduced. In Comparative Example 3, after replacing lanthanum-doped nano-cerium dioxide with undoped lanthanum nano-cerium dioxide, the wear scar diameter increased from 0.42 mm to 0.49 mm, the PB value decreased from 882 N to 823 N, and the bearing life decreased from 1850 h to 1520 h. However, the PD value remained at 3087 N, indicating that lanthanum doping enhanced the oxidation resistance and extreme pressure performance of cerium dioxide through the oxygen vacancy regulation effect. Although undoped cerium dioxide still had a certain anti-wear effect, the synergistic effect was significantly weakened. In Comparative Example 4, without the addition of microcapsule components... The wear scar diameter increased from 0.42 mm to 0.52 mm, oxidation stability deteriorated (pressure drop increased from 28 kPa to 33 kPa), and bearing life decreased from 1850 h to 1350 h. This indicates that the microcapsule components can release castor oil as needed when the oil film ruptures, timely replenishing the lubricating medium and assisting the anti-wear components in enriching and renewing in the contact area. Without microcapsules, the long-term anti-wear performance and oxidation stability both decreased significantly. In Comparative Example 5, after the mass ratio of the third anti-wear component was changed from 1:0.5:0.3 to 1:0.2:0.1, the wear scar diameter increased from 0.The wear scar diameter decreased from 0.42 mm to 0.48 mm, the PB value decreased from 882 N to 843 N, the PD value decreased from 3087 N to 2450 N, and the bearing life decreased from 1850 h to 1420 h. This indicates that when the ratio of sulfurized isobutylene and tricresyl phosphate is too low, a complete chemical reaction film and phosphate protective film cannot be formed on the friction surface, and the mechanism of the three-layer film synergistic bearing is destroyed. In Comparative Example 6, without the addition of the third anti-wear component, the dropping point decreased from greater than 320℃ to 312℃, the wear scar diameter increased from 0.42 mm to 0.61 mm, the PB value decreased from 882 N to 686 N, the PD value decreased from 3087 N to 1960 N, and the bearing life decreased from 1850 h to 1420 h. The wear time decreased significantly from 50h to 890h, indicating that the third anti-wear component (a ternary mixture of molybdenum dialkyl dithiocarbamate, isobutylene sulfide, and tricresyl phosphate) is the core component of the entire anti-wear system. The absence of this component severely degrades extreme pressure performance and anti-wear properties. In Comparative Example 7, when the third anti-wear component was only molybdenum dialkyl dithiocarbamate (excluding isobutylene sulfide and tricresyl phosphate), the wear scar diameter increased from 0.42mm to 0.58mm, the PB value decreased from 882N to 706N, the PD value decreased from 3087N to 1960N, and the bearing life decreased from 1850h to 950h. This demonstrates that the introduction of isobutylene sulfide and tricresyl phosphate significantly affects the wear resistance of the bearing. The sulfur-based chemical reaction film and the phosphorus-based phosphate protective film are indispensable; a single dialkyl dithiocarbamate molybdenum cannot achieve synergistic protection of the three films. In Comparative Example 8, after replacing the ternary composite base oil with a single polyα-olefin PAO-6, the evaporation loss at 150℃ increased from 1.65% to 2.54%, the starting torque at -40℃ increased from 0.52 N·m to 0.89 N·m, the operating torque increased from 0.21 N·m to 0.38 N·m, and the bearing life decreased from 1850 h to 960 h. This indicates that the introduction of alkyl naphthalene into the ternary composite base oil enhances the antioxidant capacity and the solubility and dispersibility of additives, while the introduction of trimellitate improves... The extreme pressure adsorption strength of the oil film is insufficient due to the inadequate dissolution and dispersion ability of the single polyalphaolefin for the extreme pressure additive, resulting in its extreme pressure performance (PB=735N) being far lower than that of the ternary base oil formulation (Example 8, PB=882N). In Comparative Example 9, after the content of each raw material component was lower than the lower limit of the range defined in this invention, the cone penetration increased from 285 (0.1mm) to 312 (0.1mm), the dropping point decreased from greater than 320℃ to 298℃, the wear scar diameter increased from 0.42mm to 0.62mm, the PB value decreased from 882N to 588N, the PD value decreased from 3087N to 1960N, and the starting torque was slightly improved (from 0.52N·m to 0.The lubricant content was 48 N·m, but the bearing life dropped significantly from 1850 h to 720 h. This indicates that when the component content is too low, the grease consistency is insufficient, the structural strength is inadequate, and the anti-wear agent concentration cannot meet the usage requirements. Although the low-temperature start-up performance is slightly improved, the overall service life is severely shortened. In Comparative Example 10, when the content of each raw material component exceeds the upper limit of the range defined in this invention, the cone penetration decreased from 285 (0.1 mm) to 245 (0.1 mm), and the wear scar diameter was slightly improved (from 0.42 mm to 0.41 mm). The evaporation loss decreased slightly (from 1.65% to 1.48%), but the starting torque at -40℃ increased from 0.52 N·m to 0.78 N·m, the running torque increased from 0.21 N·m to 0.32 N·m, and the bearing life decreased from 1850 h to 1560 h. This indicates that while some lubrication performance indicators are improved when the component content is too high, the excessively hard grease consistency leads to difficulties in low-temperature starting, and excessive additives may cause component antagonism, which may adversely affect the bearing life.

[0137] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A long-life anti-wear grease, characterized in that, It is prepared by the following steps: Step 1: Weigh the following raw material components by mass percentage: The composition consists of: 14%-22% compound calcium sulfonate thickener, 1.5%-3.5% high-alkalinity synthetic calcium sulfonate, 0.3%-1.2% surface-modified nano-calcium carbonate, 1.2%-2.8% first anti-wear component, 1.5%-3.2% second anti-wear component, 2%-4% third anti-wear component, 1%-2.5% microencapsulation component, and the balance being compound base oil. The first anti-wear component comprises modified nano-molybdenum disulfide; the second anti-wear component comprises lanthanum-doped nano-cerium dioxide; the third anti-wear component comprises a mixture of molybdenum dialkyldithiocarbamate, isobutylene sulfide, and tricresyl phosphate; the composite base oil comprises a ternary mixture of polyalphaolefin, alkyl naphthalene, and trimellitic acid ester, wherein the mass ratio of polyalphaolefin, alkyl naphthalene, and trimellitic acid ester is 1:(0.4-0.6):(0.2-0.4); and the microcapsule component comprises resin-coated vegetable oil microcapsules. Step 2: Mix the complex calcium sulfonate thickener with the complex base oil, stir, add high-alkalinity synthetic calcium sulfonate, surface-modified nano calcium carbonate, first anti-wear component, second anti-wear component, third anti-wear component, and microcapsule component, continue stirring and grinding to obtain a long-life anti-wear grease.

2. The long-life anti-wear grease according to claim 1, characterized in that, The high-base-value synthetic calcium sulfonate is a long-chain linear alkylbenzene high-base-value synthetic calcium sulfonate with a total base value of 380-450 mg KOH / g.

3. The long-life anti-wear grease according to claim 1, characterized in that, The composite calcium sulfonate thickener in step one is generated by converting high-alkalinity synthetic calcium sulfonate. The conversion process includes: (1) Weigh out high-alkalinity synthetic calcium sulfonate, composite base oil, 12-hydroxystearic acid, calcium hydroxide emulsion, acetic acid, boric acid solution and water. The mass ratio of high-alkalinity synthetic calcium sulfonate, composite base oil, 12-hydroxystearic acid, calcium hydroxide emulsion, acetic acid, boric acid solution and water is (20-30):(15-25):(2-5):(100-250):(2-5):(60-120):(10-20). (2) Mix high-alkalinity synthetic calcium sulfonate, composite base oil and acetic acid, and react; (3) Add calcium hydroxide emulsion and stir; (4) Add boric acid solution and stir; (5) Add 12-hydroxystearic acid to carry out the saponification reaction; (6) Increase the temperature to carry out the expansion reaction; (7) Increase the temperature and carry out high-temperature refining; (8) Cool down and grind and homogenize to obtain a composite calcium sulfonate thickener.

4. The long-life anti-wear grease according to claim 3, characterized in that, The high-alkalinity synthetic calcium sulfonate and the composite base oil are the same as the high-alkalinity synthetic calcium sulfonate and composite base oil in the raw material components for preparing long-life anti-wear grease.

5. The long-life anti-wear grease according to claim 1, characterized in that, The surface-modified nano-calcium carbonate includes KH560 in-situ modified nano-calcium carbonate; The KH560 in-situ modified nano-calcium carbonate is prepared by the following steps: (1) Mix silane coupling agent KH560 with an aqueous ethanol solution, adjust the pH value to 4-5, and hydrolyze to obtain silane hydrolysate; Nano-calcium carbonate was mixed with ethanol and ultrasonically dispersed to obtain a nano-calcium carbonate suspension. (2) Add the silane hydrolysate dropwise to the nano calcium carbonate suspension under stirring. After the reaction is completed, centrifuge, wash and dry to obtain KH560 in-situ modified nano calcium carbonate. The amount of silane coupling agent KH560 added is 3%-8% of the mass of nano-calcium carbonate.

6. The long-life anti-wear grease according to claim 1, characterized in that, The modified nano-molybdenum disulfide includes aminosilane-dithiocarbamate double-grafted modified nano-molybdenum disulfide. The aminosilane-dithiocarbamate dual-grafted modified nano-molybdenum disulfide is prepared by the following steps: Nano-molybdenum disulfide was added to an ethanol aqueous solution, ultrasonically dispersed, and then silane coupling agent KH550 was added to adjust the pH value to 4-5. After the reaction was completed, the mixture was centrifuged and washed to obtain an aminosilane grafted modified nano-molybdenum disulfide intermediate. The aminosilane-grafted modified molybdenum disulfide nano intermediate was dispersed in ethanol, the pH was adjusted to 9-10, carbon disulfide was added, and the reaction was carried out. After the reaction was completed, the nano-silane-dithiocarbamate double-grafted modified molybdenum disulfide nano was obtained. The amount of silane coupling agent KH550 added is 2%-4% of the mass of nano molybdenum disulfide, and the amount of carbon disulfide added is 1.5%-3% of the mass of nano molybdenum disulfide.

7. The long-life anti-wear grease according to claim 1, characterized in that, The lanthanum-doped cerium dioxide nanoparticles have a molar ratio of lanthanum to cerium of (0.05-0.15):1, and are prepared by the following steps: Weigh out cerium nitrate hexahydrate and lanthanum nitrate hexahydrate in a molar ratio of lanthanum to cerium of (0.05-0.15):1, dissolve them in deionized water, and add ammonium bicarbonate aqueous solution dropwise under stirring to carry out a precipitation reaction. At the same time, adjust the pH of the reaction system to 8-9. After the reaction is completed, centrifuge, wash, dry and calcine to obtain lanthanum-doped nano-cerium dioxide.

8. The long-life anti-wear grease according to claim 1, characterized in that, In the mixture of molybdenum dialkyldithiocarbamate, isobutylene sulfide, and tricresyl phosphate, the mass ratio of molybdenum dialkyldithiocarbamate, isobutylene sulfide, and tricresyl phosphate is 1:(0.5-1):(0.3-0.7), wherein the molybdenum content in molybdenum dialkyldithiocarbamate is 8%-12% by mass, and the sulfur content in isobutylene sulfide is 40%-48% by mass.

9. The long-life anti-wear grease according to claim 1, characterized in that, The resin-coated vegetable oil microcapsules include castor oil microcapsules coated with phenolic resin. The phenolic resin-coated castor oil microcapsules are prepared by the following steps: (1) Take phenol and formaldehyde aqueous solutions separately, mix them, add ammonia water, react to obtain water-soluble phenolic resin prepolymer; Take castor oil and emulsifier separately, add them to water, and emulsify at high speed to obtain an oil-in-water emulsion. (2) Add water-soluble phenolic resin prepolymer to oil-in-water emulsion, stir, adjust pH to 4-6, so that the prepolymer undergoes condensation reaction on the surface of oil droplets: gradually increase the temperature to 90℃ at a heating rate of 2-5℃ / min, and continue to keep the temperature for 2-4 hours after reaching 90℃. After the reaction is completed, cool naturally to room temperature, separate, wash, and dry to obtain phenolic resin-coated castor oil microcapsules.

10. The application of a long-life anti-wear grease as described in any one of claims 1-9 in automotive motor bearings.